2010
DOI: 10.1007/s12040-010-0061-2
|View full text |Cite
|
Sign up to set email alerts
|

Seaward dipping reflectors along the SW continental margin of India: Evidence for volcanic passive margin

Abstract: Multi-channel seismic reflection profiles across the southwest continental margin of India (SWCMI) show presence of westerly dipping seismic reflectors beneath sedimentary strata along the western flank of the Laccadive Ridge -northernmost part of the Chagos-Laccadive Ridge system. Velocity structure, seismic character, 2D gravity model and geographic locations of the dipping reflectors suggest that these reflectors are volcanic in origin, which are interpreted as Seaward Dipping Reflectors (SDRs).The SDRs; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 45 publications
1
13
0
1
Order By: Relevance
“…Chaubey et al (2002b) considered this basin to represent a failed rift with volcanism on a stretched continental regime, based on their deductions of rotated fault blocks akin to half graben. Considering the presence of seaward dipping reflectors (SDRs) west of the Laccadive Plateau and the derived crustal configuration from the forward modelling of the gravity data, Ajay et al (2010) inferred that the continent-ocean boundary in this region lies west of the Laccadive Plateau implying that the Laccadive Basin is continental in nature. Yatheesh et al (2013b) demonstrated that the Laccadive Basin region could be explained either in terms of a much thinned continental crust or as anomalously thick oceanic crust, based on forward modelling of the gravity profiles.…”
Section: Laccadive Basinmentioning
confidence: 99%
“…Chaubey et al (2002b) considered this basin to represent a failed rift with volcanism on a stretched continental regime, based on their deductions of rotated fault blocks akin to half graben. Considering the presence of seaward dipping reflectors (SDRs) west of the Laccadive Plateau and the derived crustal configuration from the forward modelling of the gravity data, Ajay et al (2010) inferred that the continent-ocean boundary in this region lies west of the Laccadive Plateau implying that the Laccadive Basin is continental in nature. Yatheesh et al (2013b) demonstrated that the Laccadive Basin region could be explained either in terms of a much thinned continental crust or as anomalously thick oceanic crust, based on forward modelling of the gravity profiles.…”
Section: Laccadive Basinmentioning
confidence: 99%
“…6) was constructed in order to constrain the seismic interpretation with crustal densities derived from refraction velocities obtained in the southern South Atlantic margin (Leyden et al 1971), average velocities for volcanic and igneous rocks related to the Serra Geral and Entendeka large igneous provinces, refraction from SDR edges offshore India (e.g. Ajay et al 2010), and lower crust mantle refraction velocities obtained from different sources in the oceanic realm. The gravity and magnetic anomalies cross-plotted along the profile (Fig.…”
Section: Crustal Architecturementioning
confidence: 99%
“…The average thickness of these layers in each domain, i.e., Laccadive Basin, ATTC and continental shelf/slope, were assumed using the seismic section/drill hole information as guide. The densities for these sediment layers were estimated based on the velocityedensity relationship of Ludwig et al (1970) Some researchers (Biswas and Singh, 1988) considered this region to be underlain by oceanic crust, while others Ajay et al, 2010) considered a thinned continental crust. We also noted that no dependable constraints, such as, crustal velocity structure based on seismic studies or identified seafloor spreading type magnetic anomalies, are available to resolve the ambiguity about the nature of crust underlying the Laccadive Basin.…”
Section: Interpretation Of Gravity Anomaliesmentioning
confidence: 99%